The Rules and Criteria in Recognizing of Fabricated Hadiths: on Ibn Qayyim Through His Book Manarul Munif | ضوابط معرفة الحديث الموضوع عند ابن القيم في كتابه المنار المنيف - Ade Pahrudin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
Fabrication of hadith is a problem that has existed since the beginning of Islam until now with various reason, this article describes the methodology used by Ibn Qayyim through his book Manarul munif that contain rules and criteria in recognizing of fabricated hadiths in the study of matn hadith criticism. This indicates the moslem scholars have studied seriously the study of matn hadith criticism to maintain the validity of a tradition in addition to criticism sanad hadith.